PENDING CLAIMS IN OUTPATIENT SCHIZOPHRENIA CASES AT RSKJ SOEPRAPTO BENGKULU PROVINCE - Widyawati, Dwi; Heltiani, Nofri (Jurnal Saintifik (Multi Science Journal), 2024)
Incompleteness of files and inaccurate diagnosis codes are factors that cause claims to occur. From the results of observations of 10 samples of claim files for outpatient schizophrenia cases, it was found that 3(30%) were approved and 7(70%) were rejected because 2 files had different SEP dates, 2 files did not have the signature of the doctor in charge of the patient on the medical resume sheet and 3 used incorrect diagnosis codes, resulting in delays in the payment process which caused material losses for the Hospital. This study aims to determine pending claims for outpatient schizophrenia cases in terms of completeness of files and accuracy of diagnosis codes. The type of research is observational with a quantitative descriptive design with a population and sample of 68 pending outpatient schizophrenia case files for the period January and February 2024. The research data used is secondary data obtained by observation using an observation sheet, then the data is processed and analyzed univariately using a frequency distribution. The results of this research show that pending claims for outpatient schizophrenia are seen from the completeness of the file and the accuracy of the diagnosis code, namely 16 (23%) pending due to incomplete claim files, 48 ​​(71%) pending due to inaccurate diagnosis codes and 4 (6%) pending due to incomplete and inaccurate diagnosis code. Efforts are needed to solve the problem of pending claims by forming an internal verification team to evaluate and optimize existing management activities and communicate with the person in charge of the medical department